Ketersediaan APD (Alat Pelindung Diri) dan Pengawasan IPCLN (Infection Prevention and Control Link Nurse) terhadap Pelaksanaan Kewaspadaan Standar Rumah Sakit - Eliza Hafni; Siti Saidah Nasution; Etti Sudaryati (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the relationship between the availability of PPE (Personal Protective Equipment) and IPCLN (Infection Prevention and Control Link Nurse) supervision in the implementation of hospital standards. This type of quantitative research uses a descriptive correlation and observational design with cross-sectional observations. The results showed that the availability of PPE and IPCLN supervision were significantly related to standard precautions. The variable of PPE availability is 24,363, while the IPCLN supervision variable is the regression coefficient value of OR 27,904. In conclusion, there is a significant relationship between the availability of PPE and IPCLN in implementing standard precautions in private hospitals in the city of Medan. Keywords: Availability of PPE, Standard Precautions, IPCLN Supervision